Design and Implementation of a Shined Length Periodic Microstrip Antena for 2.4 GHz and 5.8 GHz Double Wi-Fi - Putri Rahmadini; Aprinal Adila Asril; Ramiati Adila Asril; Ashilah Khairunnisa Putri (Politeknik Negeri Padang, 2026)
This research aims to design and implement a twin slit rectangular microstrip antenna for 2.4 GHz and 5.8 GHz dual-band Wi-Fi using CST Studio Suite 2019 software and in antenna measurements using a Vector Network Analyzer. Some of the antenna parameters produced are return loss, bandwidth, VSWR, radiation pattern, and gain. This antenna has an antenna size of 45 x 53 mm. The antenna is designed based on the characteristics of several antenna parameters, namely having a return loss ≤-10 dB gain value ≥1 dB, and VSWR ≤2. The type of substrate used is FR-4 (lossy) with a dielectric constant specification of 4.3, a characteristic impedance of 50 ohms, and a thickness of 1.6 mm. The ground plane material used is copper with a thickness of 0.035 mm. The microstrip antenna parameter optimization results are in the form of a return loss of -13.64 dB with a frequency of 2.4 GHz and -30.40 dB with a frequency of 5.8 GHz, VSWR values of 4.38 with a frequency of 2.4 GHz and 5.45 with a frequency of 5.8 GHz and have unidirectional pola radiation. In comparison, the return loss value of the fabricated antenna is obtained at -4.52 dB at a frequency of 2.5 GHz and -6.32 dB at a frequency of 5.8 GHz. VSWR values of 4.38 at a frequency of 2.4 GHz and 5.45 at a frequency of 5.8 GHz.